The Impact of Non-Formal Education on Human Capital: A Generational Approach - Marina N. Kicherova; Galina Z. Efimova (National Research Mordova State University, 2020)
Introduction. The update rate of information and the scope of social transformations became a trend of modern life. To remain competitive, a person needs to foster his/her competencies and skills. Non-formal education is becoming the most mobile way to solve the tasks, allowing to quickly acquire relevant knowledge and experience. Research interest is focused on the impact of non-formal education on the formation and development of the human capital. The purpose of the article is to study the involvement of representatives of various generations in a non-formal education. Materials and Methods. The research draws on the methodology of the in-depth interview interpretation analysis. The data was obtained using the focus group method: a series of 27 group interviews, 9 for each age category (youth, mature and older). The focus groups included 253 people - residents of Tyumen, Tobolsk, Ishim, and settlements in the South of the Tyumen region. Results. The possibilities of non-formal education in the process of accumulation and realization of human capital were revealed. The analysis of the practices of youth, adult and older generation's non-formal education was carried out. Based on the study of generational theories, the educational attitudes of various age groups and the needs for non-formal learningwere analyzed. Based on the analysis of the intensity of educational practices, three types of actors were identified depending on their involvement in non-formal education: the active type "eternal student", the moderate type "situational student" and the passive type "indifferent student", which were found in representatives of different generations. The authors identified the following things that motivate and demotivate people to receive non-formal education: operational updating of competencies, fostering of personal and professional skills for a specific professional position, reducing the qualification gap. Analysing the non-formal educational practices of youth, adults, and the older generation, the authors found that non-formal education significantly affects the dynamics of professionalization, the nature of social and labour transfers. Discussion and Conclusion. The results of the study will aid in sizing the impact of non-formal education on human capital in terms of the generational approach. The materials of the article are useful for building an educational ecosystem at the regional and national level and for practical application in the development and adjustment of strategies for working with people of different age groups.